The minimization of open stacks problem: A review of some properties and their use in pre-processing operations - Yanasse, Horacio Hideki; Senne, Edson Luiz França [UNESP] (Elsevier B.V., 2010)
Pre-processing operations that reduce the size of a problem may be decisive for solving or not solving practical instances of a NP-hard problem. In this article we review some properties suggested in the literature for the minimization of open stacks problem that can be used in pre-processing operations to reduce the instances sizes. We also present a new pre-processing technique that may be very effective in reducing the size of an instance. We present computational tests with the suggested pre-processing operations applied on sets of MOSP instances of the literature and we show that the reductions obtained can be significant. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Combinatorial optimization; Minimization of open stack problem; Pre-processing; Size reduction